The Value of Life from the Poem "Senja Di Pelabuhan Kecil " by Chairil Anwar with a Mimetic Approach - Triaviranda, Triaviranda; Sari, Diana Permata; Yolanda, Esti; Nasution, Jamila; Samosir, Jusca Santanovalina; Rosmawaty, Rosmawaty (EDUCTUM: Journal Research, 2024)
Literary works are works composed of the author's thoughts and feelings which describe imaginative thoughts and then express them into a work in oral or written form. Poetry is a text consisting of lines. The mimetic approach is an approach that views fictional prose as a human creation written based on materials taken from the universe. The aim of this research is to find out the meaning in Chairil Anwar's poetry and to improve the writer's understanding of the mimetic approach. The research method used in analyzing this poetry is the qualitative descriptive method. Based on the results of the analysis of the poem "Sunja Di Pelabuhan Kecil" it can be concluded that this poem contains the meaning of sadness about loss and the lesson taken from this poem is that as humans we must remain sincere about all destiny because in this world nothing is eternal.